MAKNA KONTEKSTUAL LEKSEM HAI DALAM KOMIK DETEKTIF CONAN KARYA AOYAMA GOSHO - KURNIAWAN, DAVID (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is needed by human being because by language human can get their needsby communicating eachother.  As a verbal communication, language is a sound symbolwhich is arbitrary . the statement beforeencourages to study one of the lexeme of japaneselanguage which is often heard or known by Indonesian people,that is hai. Based on that, thissudy will analyze the research problem : (1) what are the hai contextual lexeme in detectiveconan comic volume 59, 63, and 64. (2) how to use the hai contextual lexeme in detectiveconan comic volume 59, 63, and 64. The source of this research taken from detective conan comic by aoyama gosho. Thecomic used because the story reflects the daily life, the lnguage used is also simple, and easyto be understood by every reader from children to adult. The data taken was dialogue whichcontains hai lexeme. Therefore, the researcher used descriptive qualitative method which is amethod that describes the phenomena where the activity is studied and then the conclusion ismade. This method is used to analyze the hai menaing in detective conan meaning. The mainreason of using this method is to show the fact, the condition, and the phenomenon thathappens when this research is done. In this detective conan comic, the researcher found sixty nine dialogues that containshai lexeme. From those three volume of the comic, the researcher found twenty nine hailexeme which means koutei, twenty one which means shoudake, twelve h ai lexeme whichmeans outou, three hai lexeme which means aizuchi, three hai lexeme which means kanki,and there is no hai l exeme that means tsuinin. Besides, from 5 hai meaning that is found,there are difference in the usage of hai lexeme, which are confirmation, approval on demand,approval on requirement, approval on invitation, answer when called, respond to informationsubmitted, and attract attention. for the next research, it is expected to find more source ofdata so the usage of hai lexeme can be found more complete. Keywords : lexeme, semantic, contextual